A surgical strategy for severe facial asymmetry due to unilateral condylar overgrowth. Issue 5 (May 2016) - Kim, H.-S.; Kim, J.-Y.; Huh, J.-K.; Park, K.-H.
Abstract: Unilateral condylar overgrowth induces severe facial asymmetry. Therefore, treatment focuses on both elimination of the condyle lesion and correction of the facial asymmetry. The aim of this report is to present three patient cases, introducing a simpler surgical method, the indications for this surgical method, and a treatment planning flow that is consistently applicable regardless of the origin of the condylar lesion. Condylectomy was performed simultaneously with orthognathic surgery, with the vertical ramus osteotomy selected as the method of ramus surgery; ipsilateral ramus surgery was not performed on the condylectomy side. This method is applicable in cases in which facial asymmetry originates solely from unilateral condylar overgrowth, and the maxilla and mandible are presumed to have been in the normal class I anteroposterior position before the onset of condylar lesion growth. After surgery, temporomandibular joint pain and/or mouth limitations were resolved, the new condyle showed satisfactory bone remodelling, and favourable facial symmetry was attained. The postoperative results were maintained long-term and there was no recurrence on the condylectomy side. This simply modified surgical strategy for facial asymmetry due to unilateral condylar overgrowth may be used in selected patients, regardless of the origin of the condylar lesion.